CONTRIBUTION OF AGRICULTURE TO THE DEVELOPMENT OF SERBIA - Mitrović, Slavka; Mitrović, Aleksandra; Cogoljević, Maja (Economics of Agriculture, 2017)
The Republic of Serbia has signifcant resources for the development of agriculture (natural, scientifc and professional). However, agriculture doesnt achieve the results adequate to conditions it has and which are expected of it. The aim of the research in this paper is to perceive the contribution of agriculture in the development of Serbia. The contribution of agriculture was considered by an analysis of next indicators: 1. Share of rural population in total population and an active rural population in the total work force, 2. Share of agriculture in the creation of gross domestic product (GDP) and, 3. Contribution of agriculture and agro-industry to the foreign trade exchange. The analysis of the mentioned indicators points out that our developmental strategy must be based on the increase of agricultural-food products export (intensive production), and the change in production structure in accordance with the solvent demand (especially for the demand of ecologically healthy food) and which level of fnalization would be higher, in order to increase competitiveness and a new value. In this paper were used published data of the Statistical Offce of the Republic of Serbia, and then the research results of some authors in this feld, as well as the results of the authors other research. The research period was from the year 2000 to the year 2015. In the analysis of contribution (performances) of agriculture were used the system and comparative analysis, as well as the standard statistical – mathematical instrumentation: average values, a rate of change and a coeffcient of determination. In the paper were presented also the linear trends of GDP and income of agriculture and a share of agriculture in GDP, as well as the export/import of whole economy and agriculture trends.